Copyright in the Art Industry: Ethical and Management Challenges for Artwork Protection - Darmantho, Adhitya (Universitas Negeri Semarang, 2024)
Indonesia, with its diversity of arts and culture, faces unique challenges in copyright protection in the digital era. Globalization and digital technology have transformed the landscape of the arts industry, introducing both new opportunities and complex risks. The aim of this research is to explore the ethical and managerial issues related to copyright protection of artistic works in Indonesia. This study employs a qualitative approach with a focus on literature review. Copyright protection in the Indonesian arts industry encounters several challenges, including ineffective law enforcement, the gap between technological advancements and regulations, and the need for more adequate legal infrastructure. The importance of enhancing legal awareness and public education, as well as the necessity of collaboration among government, relevant institutions, and the industry in addressing these challenges, cannot be underestimated. Furthermore, adaptive regulatory updates and responsiveness to technological advancements, the enhancement of ethical awareness in the use of artistic works, and the implementation of cutting-edge technologies such as artificial intelligence and blockchain are strategic steps in strengthening copyright management.